Preventive Behaviors Related to Covid-19 Among High School Students: Cross-Sectional Web-Based Survey - Fika Muntahaya; Thoriq Fajar Batuah; Hoirun Nisa (Poltekkes Kemenkes Jakarta III, 2021)
The increasing number of COVID-19 cases encourages the need for health efforts from various parties. Palangka Raya City is one of three cities with a high risk status in Central Kalimantan Province, while the surrounding area is currently at medium risk. In line with that, data on confirmed cases of COVID-19 in Palangka Raya City also occupies the highest position in the province of Central Kalimantan. The Ministry of Education, through its circular, urged the implementation of 3M education, namely wearing masks, washing hands, and maintaining distance, in order to stop the transmission of COVID-19. The purpose of this study was to describe knowledge, attitudes and behavior regarding the prevention of COVID-19 in students of MAN Kota Palangka Raya in 2020. This study used a cross-sectional study design with a total number of respondents of 339 students. Data collection was carried out via google form in October 2020. The results of the analysis showed that 98.8% of students had good knowledge of COVID-19 and 87.0% of students had a positive attitude regarding the prevention of COVID-19, but only 54.6% of students had good COVID-19 prevention behavior. 3M's preventive behavior education efforts still need to be improved in an effort to stop the spread of COVID-19. Future researchers are expected to explore factors related to COVID-19 prevention behavior in adolescents.